Radioluminescent Ionic Liquids: Designer Materials for Detecting and Quantifying Ionizing Radiation - Rodrigues Ferreira Maltez, Dario Pablo (2020)
A designed radioluminescent ionic liquid (RadIL), composed of a single imidazolium cation and two different fluorescent anions, is presented. The material allows the conversion of the energy released by energetic charged particles into visible light by radiofluorescence. Its capability in detecting and in quantifying alpha and beta particles was proved by its use as a solvent in liquid scintillation counting. A keynote of this performance is that its radioluminescence yield strongly depends on temperature. This feature represents a clear advantage compared with common commercial scintillators composed of organic volatile solvents that cannot be usually heated. The temperature dependence of the radioluminescent material allows the disentangling of the Cherenkov and radiofluorescence contributions emerging from samples containing one or more radionuclides. This property can be used for alpha/beta quantification in radionuclide mixtures, following a precalibration of the material response to each radionuclide present in the blend. This RadIL represents the first precedent of an innovative family of luminescent ILs to be developed. The rational design of these materials opens interesting possibilities of real-time quantifications of fission products during the reprocessing of spent nuclear fuels.